Rethinking Corporate Restructuring through Strategic Openness: A Qualitative Synthesis of Emerging Approaches and Policy Implications - Seger Santoso; Grace Yulianti (LPPM STIE Kasih Bangsa, 2024)
This qualitative literature review explores how strategic openness reshapes corporate restructuring practices, particularly in contexts of financial distress and institutional change. Drawing on recent empirical and conceptual studies, the review synthesizes findings from over 60 peer-reviewed sources to examine the impact of transparency, stakeholder engagement, and participatory strategy-making on organizational turnaround. The study reveals that openness fosters reflexive capabilities, enhances legitimacy, and enables adaptive strategic responses to crisis. However, it also uncovers tensions such as coordination complexity and the paradox of urgency versus inclusivity. The findings contribute to a broader understanding of open strategy as a viable governance mechanism in restructuring regimes and offer policy insights for integrating participatory principles into corporate recovery frameworks. This review emphasizes the importance of openness as a strategic capability that can facilitate resilient and sustainable organizational renewal in turbulent environments